Potential Factors for Psychological Symptoms at Three Months in Patients with Young Ischemic Stroke. (9th February 2021) - Xu, Dongjuan; Chu, Xi; Wang, Kun; Wei, Lianyan; Xu, Yunyun; Huang, Xiaomin; Li, Jinna; Xu, Lina; Yin, Lu; Liu, Hong; Liu, Xiaolei; Leng, Haixia; et al.
Abstract : Objective. Psychological status plays a vital role in the recovery in young ischemic stroke patients. However, few reports on the psychological symptoms in Chinese young ischemic stroke patients have been published. In the present study, we aimed to outline the psychological status of young ischemic stroke patients and its risk factors at three months after their stroke. Methods. 364 patients with young ischemic stroke and 384 age-matched healthy controls were consecutively recruited from our study hospitals of the mainland of China between June 2018 and November 2020. Social demographic and clinical data were collected from all enrolled participants in the acute stage of their stroke, and their psychological variables were assessed via the Symptom Checklist 90 Revised (SCL-90-R) at three-month timepoint after their stroke. Multivariable logistic regression analyses were run to identify the independent factors for psychological variables in patients. Results. Compared with healthy controls, patients with young ischemic stroke had significantly higher total score of SCL-90-R and all subscale total scores (p < 0.01 or 0.05). 22.3% (81/364 cases) in young ischemic stroke patients had psychological abnormalities. Compared with young ischemic stroke patients without psychological symptoms (n = 283 ), patients with psychological symptoms (n = 81 ) had higher rate of married status (p = 0.03 ), rate of hypertension (p = 0.01 ), infarct size (p = 0.01 ), and the family dysfunction (p < 0.01 ). Multivariate logistic regression analyses revealed that the family dysfunction (odds ratio [OR], 2.50, 95% confidence interval [CI]: 1.71 to 3.54, p < 0.01 ), having hypertension (OR, 3.27, 95% CI: 1.92 to 4.27, p = 0.02 ), and ≥20mm 3 infarct size (OR, 2.39, 95% CI: 1.53 to 3.45, p < 0.01 ) were independent factors for having psychological abnormalities in patients with young ischemic stroke at three months after their stroke. Single (OR, 1.23, 95% CI: 1.03 to 1.54, p = 0.01 ), poor family function (OR, 1.21, 95% CI: 1.05 to 1.45, p = 0.03 ), and ≥20mm 3 infarct size (OR, 1.74, 95% CI: 1.14 to 3.13, p = 0.02 ) were independent factors for having depression in patents with psychological symptoms. The family dysfunction (OR, 2.32, 95% CI: 1.51 to 2.80, p < 0.01 ) and hypertension (OR, 2.41, 95% CI: 1.54 to 3.46, p = 0.03 ) were independent factors for emerging somatization and anxiety in patients with psychological symptoms, respectively. Conclusions. At three months after their stroke, young ischemic stroke patients had psychological problems and risk factors for developing them.